2020
DOI: 10.1371/journal.pone.0237566
|View full text |Cite
|
Sign up to set email alerts
|

Effects of teriparatide and bisphosphonate on spinal fusion procedure: A systematic review and network meta-analysis

Abstract: Background Giving patients anti-osteoporotic agents peri-operatively is a well-accepted strategy to increase fusion rate and prevent complications. The purpose of this study was to investigate effectiveness of teriparatide and bisphosphonate on fusion surgery of thoracic and lumbar spine. Methods We searched EMBASE and PubMed for randomized clinical trials (RCTs) and prospective comparative studies using teriparatide or bisphosphonate in peri-operative spinal fusion surgery. Our synthesized data of fusion rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
0
11
0
1
Order By: Relevance
“…Compared with a previous meta-analysis [ 25 ], we compared more parameters to evaluate the effect of BP therapy on lumbar fusion surgery and obtained some new findings, which indicated that compared with controls, BPs can significantly reduce VCF, cage subsidence, and loosening of pedicle screws after lumbar fusion surgery. Although the quality of included studies was relatively high, but we should also take consider the limitations listed below.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with a previous meta-analysis [ 25 ], we compared more parameters to evaluate the effect of BP therapy on lumbar fusion surgery and obtained some new findings, which indicated that compared with controls, BPs can significantly reduce VCF, cage subsidence, and loosening of pedicle screws after lumbar fusion surgery. Although the quality of included studies was relatively high, but we should also take consider the limitations listed below.…”
Section: Discussionmentioning
confidence: 99%
“…Although several animal studies on spinal fusion have reported a positive effect of BPs [ 21 , 22 ], two recent clinical studies concluded that preoperative BPs had no effect on the nonunion rates [ 20 , 23 ], and one systematic review did not clearly determine whether BP therapy after surgery provided an added benefit after lumbar fusion surgery [ 24 ]. A recent meta-analysis has evaluated the effect of postoperative BPs on the fusion rate [ 25 ], but the major objective was comparing teriparatide and BPs, and the comparisons in this study were not sufficiently comprehensive.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with a previous meta-analysis [25], we compared more parameters to evaluate the effect of BP therapy on lumbar fusion surgery and obtained some new ndings, which indicated that compared with controls, BPs can signi cantly reduce VCF, cage subsidence and loosening of pedicle screws after lumbar fusion surgery. Although the quality of included studies was relatively high, but we should also take consider the limitations listed below.…”
Section: Discussionmentioning
confidence: 99%
“…Although several animal studies on spinal fusion have reported a positive effect of BPs [21,22], two recent clinical studies concluded that preoperative BPs had no effect on the nonunion rates [20,23], and one systematic review did not clearly determine whether BP therapy after surgery provided an added bene t after lumbar fusion surgery [24]. A recent meta-analysis has evaluated the effect of postoperative BPs on the fusion rate [25] , but the major objective was comparing teriparatide and BPs, and the comparisons in this study were not su ciently comprehensive.…”
Section: Introductionmentioning
confidence: 99%
“…Für Teriparatid sind die Ergebnisse generell einheitlicher und schließen auch die Fusion ein, möglicherweise auf Basis des Wirkmechanismus der direkten Erhöhung des BMD. Es ergibt sich also ein positiveres Bild für die Nutzung von Teriparatid zur Verhinderung von mechanischen Komplikationen [11,12]. Mittlerweile findet auch zunehmend Denosumab, als Anti-RANKL-Antikörper, Anwendung in der Osteoporose-Therapie.…”
Section: Präoperative Möglichkeitenunclassified